Hipopótamos en Colombia: una aproximación a la problemática de invasión y las opciones de manejo (2020)
Introduced species are seen as a threat to biodiversity and human population among the places on which they arrive. Such is the case for Hippopotamus amphibius in Colombia, its arrival more than 30 years ago, raises questions on possible ecological and social damage among with species management. The goal of the present work is to cover the current situation concerning hippopotamuses as an invasive species in Colombia. For this purpose the general characteristics of of the species have been approached along with its introduction, establishment and expansion over the country, the possible cost/benefit of its presence in colombian ecosystems and lastly, the management options that have been proposed for the hippopotamuses as an invasive species.